Organizational Culture and Impact on Improving Employee Performance - Misbachul Munir; Samsul Arifin (Journal of Social Science Studies (JOS3), 2021)
The policy of the management in the organization is to introduce organizational culture to its employees which will help employees to get to know the organizational system as a whole and integrated with work behavior. A proper understanding of organizational culture must lead to an increase in employee performance and is a contribution to the realization of organizational goals. Organizational culture needs to be developed in such a way as to improve employee performance and continuously develop quality awareness. Thus, the purpose of this study is to analyze and determine the influence of organizational culture on employee performance. The research was conducted in a small business that trades through online media and has 17 employees. The data analysis technique used a simple regression test. The results of this study mostly show a positive relationship between a strong culture and improved performance. Based on this research, it can be concluded that organizational culture has a positive and significant effect on employee performance.